2024
DOI: 10.1002/advs.202309852
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Phosphatase Substrate Preference for Controlled Biosynthesis Using a “Design–Build–Test–Learn” Framework

Jiangong Lu,
Xueqin Lv,
Wenwen Yu
et al.

Abstract: Biosynthesis is the application of enzymes in microbial cell factories and has emerged as a promising alternative to chemical synthesis. However, natural enzymes with limited catalytic performance often need to be engineered to meet specific needs through a time‐consuming trial‐and‐error process. This study presents a quantum mechanics (QM)‐incorporated design–build–test–learn (DBTL) framework to rationally design phosphatase BT4131, an enzyme with an ambiguous substrate spectrum involved in N‐acetylglucosamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Bian et al 15 demonstrated that terpene synthases with substrate promiscuity are widespread and enhanced the production of certain terpenoids in Escherichia coli exploiting engineered mutants. Lu et al 16 reshaped the substrate-binding pocket of phosphatase BT4131 and switched its substrate preference from glucose-6phosphate to N-acetylglucosamine-6-phosphate, promoting the biosynthesis of N-acetylglucosamine in microbial cell factories. Sequence and structural analyses were used to investigate ISY's substrate preference for progesterone, 2cyclohexen-1-one, and 5.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bian et al 15 demonstrated that terpene synthases with substrate promiscuity are widespread and enhanced the production of certain terpenoids in Escherichia coli exploiting engineered mutants. Lu et al 16 reshaped the substrate-binding pocket of phosphatase BT4131 and switched its substrate preference from glucose-6phosphate to N-acetylglucosamine-6-phosphate, promoting the biosynthesis of N-acetylglucosamine in microbial cell factories. Sequence and structural analyses were used to investigate ISY's substrate preference for progesterone, 2cyclohexen-1-one, and 5.…”
Section: ■ Introductionmentioning
confidence: 99%